Failure assessment of aluminum liner based filament-wound hybrid riser subjected to internal hydrostatic pressure - Dikshit, Vishwesh (2018)
The present study describes the burst behavior of aluminum liner based prototype filament-wound hybrid riser under internal hydrostatic pressure. The main objective of present study is to developed an internal pressure test rig set-up for filament-wound hybrid riser and investigate the failure modes of filament-wound hybrid riser under internal hydrostatic burst pressure loading. The prototype filament-wound hybrid riser used for burst test consists of an internal aluminum liner and outer composite layer. The carbon-epoxy composites as part of the filament-wound hybrid risers were manufactured with [±55o] lay-up pattern with total composite layer thickness of 1.6 mm using a CNC filament-winding machine. The burst test was monitored by video camera which helps to analyze the failure mechanism of the fractured filament-wound hybrid riser. The Fiber Bragg Grating (FBG) sensor was used to monitor and record the strain changes during burst test of prototype filament-wound hybrid riser. This study shows good improvements in burst strength of filament-wound hybrid riser compared to the monolithic metallic riser. Since, strain measurement using FBG sensors has been testified as a reliable method, we aim to further understand in detail using this technique.